Contrasting links between growth and survival in the early life stages of two flatfish species - Primo, Ana Ligia (2021)
Understanding the causes of variation in recruitment of marine fishes has been a central goal over the last century. However, the relationship between year class strength and larval growth and survival is poorly known for most species. The main goal of this study was to investigate the relationships between larval traits and year class strength of two flatfish species in an nursery estuary. We examined the effects of the variation in the early life characteristics (pelagic larval growth, pelagic larval duration, size-at-hatching and size-at-settlement) on post-settlement survival of flounder Platichthys flesus and common sole Solea solea in the Mondego estuary (Portugal) over a 5-year period (2011–2015). The two flatfish species showed distinct larval traits variation during the study period, mainly related with location of the spawning ground and intrinsic biologic patterns. Flounder was able to delay metamorphosis while gathering energy and/or waiting for suitable environmental cues from estuarine origins while sole take advantage of better environmental conditions due to a later hatching. Early fast growth were strongly related with subsequent growth, affecting larval survival. Both growth and larval traits variation during the studied period were strongly related with temperature. This study highlights the importance of early growth for fish survival and contributes with key information on fish early life stages that will support a better management of fish stocks.